Skin Barrier using Aloe Vera and Olive Oil on Prevention of Incontinence Associated Dermatitis in Immobility Patients - Ira Maulani Lubis; Kiking Ritarwan; Asrizal Asrizal (Universitas Aisyah Pringsewu, 2022)
Background: Incontinence Associated Dermatitis is an inflammation of the skin that occurs when urine or feces comes in contact with the perineum. The use of a skin barrier that contains moisturizers can prevent skin inflammation. The mechanism of action of moisturizers is found in aloe vera and olive oil, as well as accelerating wound healing, anti-inflammatory, and antimicrobial. Objective: To identify the effect of skin barrier aloe vera and olive oil on the prevention of Incontinence Associated Dermatitis in immobility patients. Methods: The study was a Quasi-Experiment post-test-only comparison group design. The population was newly admitted immobility patients without Incontinence Associated Dermatitis. A sample of 66 people was divided into the control group and the intervention group, sampling using purposive sampling, analyzed using the Mann Whitney and Kruskal Wallis tests. Results: The results showed that there were differences in the values of the three groups, namely the aloe vera, olive oil, and control groups (p = 0.003), with the highest control mean value. Conclusion: This study revealed that immobility patients who were not given the skin barrier using aloe vera or olive oil experienced the most Incontinence Associated Dermatitis. Abstrak: Latar belakang: Incontinence Associated Dermatitis adalah peradangan kulit yang terjadi ketika urin atau tinja kontak dengan perineum. Penggunaan skin barrier yang mengandung pelembab dapat mencegah peradangan kulit. Mekanisme kerja pelembab terdapat pada aloe vera dan olive oil, sekaligus dapat mempercepat penyembuhan luka, antiinflamasi, dan antimikroba. Tujuan penelitian: Untuk mengidentifikasi pengaruh skin barrier aloe vera dan olive oil terhadap pencegahan Incontinence Associated Dermatitis pasien imobilitas. Metode: Jenis penelitian adalah quasi-eksperiment dengan post-test only comparison group design. Populasi adalah pasien imobilitas yang baru masuk tanpa incontinence associated dermatitis. Sampel sebanyak 66 orang dibagi dalam kelompok kontrol dan kelompok intervensi, pengambilan sampel menggunakan purposive sampling, dianalisa menggunakan uji Mann Whitney dan Kruskal Wallis. Hasil: Menunjukkan terdapat perbedaan nilai ketiga kelompok, yaitu kelompok aloe vera, olive oil dan kontrol (p=0,003), dengan nilai rata-rata kontrol paling tinggi. Kesimpulan: Penelitian ini mengungkapkan bahwa pasien imobilitas yang tidak diberikan skin barrier aloe vera maupun olive oil paling banyak mengalami incontinence associated dermatitis.